2002
DOI: 10.1200/jco.2002.09.091
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumoral Thymidylate Synthase and p53 in Metastatic Colorectal Cancer Patients Receiving Fluorouracil-Based Chemotherapy: Phenotypic and Genotypic Analyses

Abstract: P r o g n o s t i c V a l u e o f T u m o r a l T h y m i d y l a t e S y n t h a s e a n d p 5 3 i n M e t a s t a t i c C o l o r e c t a l C a n c e r P a t i e n t s R e c e i v i n g F l u o r o u r a c i l -B a s e d C h e m o t h e r a p y : P h e n o t y p i c a n d G e n o t y p i c A n a l y s e sBy Marie-Christine Etienne, Maurice Chazal, Pierre Laurent-Puig, Nicolas Magné, Christophe Rosty, Jean-Louis Formento, Mireille Francoual, Patricia Formento, Nicole Renée, Emmanuel Chamorey, André Bourgeon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 25 publications
5
79
2
4
Order By: Relevance
“…Patients with *2/*2 genotype have a good prognosis, but patients with *3/*2 genotype are sometimes included in the good prognosis group 27 and other times in the intermediate or bad prognosis group. 12,26 In a recent work, Uchida et al 29 reported that the loss of heterozygosity at the TS locus in tumor samples of colorectal cancer patients treated with fluoropyrimidine therapy affects tumor response and survival in those patients with a heterozygous TS*2/*3 genotype. In 17 of 22 of these heterozygous cases, a LOH was demonstrated in tumor tissues The authors reported that the response rate of the TS*2/loss tumor genotype patients was 80% and that only 1 of 7 tumors with a genotype of *3/loss showed a response.…”
Section: Correlation Between Ts Genotype and Survivalmentioning
confidence: 99%
“…Patients with *2/*2 genotype have a good prognosis, but patients with *3/*2 genotype are sometimes included in the good prognosis group 27 and other times in the intermediate or bad prognosis group. 12,26 In a recent work, Uchida et al 29 reported that the loss of heterozygosity at the TS locus in tumor samples of colorectal cancer patients treated with fluoropyrimidine therapy affects tumor response and survival in those patients with a heterozygous TS*2/*3 genotype. In 17 of 22 of these heterozygous cases, a LOH was demonstrated in tumor tissues The authors reported that the response rate of the TS*2/loss tumor genotype patients was 80% and that only 1 of 7 tumors with a genotype of *3/loss showed a response.…”
Section: Correlation Between Ts Genotype and Survivalmentioning
confidence: 99%
“…Therefore, the TS functional polymorphisms are under investigation for the possibility of optimising chemotherapy (Yong and Innocenti, 2007). Studies in patients with metastatic colorectal cancer showed that carriers of the TS 5 0 -UTR 3R (3G) and/or the TS 3 0 -UTR 6 þ alleles had adverse clinical outcomes (Pullarkat et al, 2001;Etienne et al, 2002;Park et al, 2002;Marcuello et al, 2004;Stoehlmacher et al, 2004;Martinez-Balibrea et al, 2007); however, such an association was not always detected (Lecomte et al, 2004;Jakobsen et al, 2005;Ruzzo et al, 2007a, b). Heterogeneity in clinical experimental conditions (Sorbye et al, 2007), in tumour burden (Köhne et al, 2002) and in genetic/molecular features in the presence of a multisite metastatic disease (Yokota, 2000) may explain variable results in these pharmacogenetic studies.…”
mentioning
confidence: 99%
“…An association between the genotype of the TS enhancer region and response and toxicity with 5-FU-based therapy in patients with colorectal cancer has been reported previously. [29][30][31][32][33][34][35][36][37][38][39] : patients who are homozygous for the double-tandem repeat have a lower TS protein content and a higher likelihood of response, but a greater risk of toxicity. MTHFR is involved in the regeneration of 5 methyltetrahydrofolate from 5,10 methylenetetrahydrofolate.…”
Section: Discussionmentioning
confidence: 99%